EFEKTIVITAS IMPLEMENTASI KERJASAMA INDONESIA-FILIPINA DALAM MENANGANI PENYELUNDUPAN NARKOTIKA TAHUN 2017-2022 - Nadirah, Nadirah; Prabandari, Sherlly Merisa Tri (Moestopo Journal of International Relations (MJIR), 2024)
This research analyzes the effectiveness of Indonesia–Philippines cooperation in combating narcotics smuggling during the 2017–2022 period. The main objective is to assess the extent to which bilateral memoranda of understanding—between institutions such as the Indonesian National Police (POLRI) and Philippine National Police (PNP), as well as the National Narcotics Agency (BNN) and the Philippine Drug Enforcement Agency (PDEA)—have been effectively implemented in addressing transnational narcotics crimes. The study employs a qualitative descriptive method, utilizing data from interviews and literature review of relevant secondary sources. Theoretical analysis is based on Steers’ (2015) organizational effectiveness framework, emphasizing accuracy, timeliness, objectivity, and comprehensiveness of execution. Findings indicate that the cooperation is moderately effective in supporting enforcement and prevention efforts, although it has not fully disrupted cross-border drug networks. Key challenges include limited coordination during the COVID-19 pandemic, the evolving complexity of smuggling operations, and legal system differences. Nevertheless, increased intelligence sharing, joint policing efforts, and the establishment of a bilateral committee demonstrate that this partnership has contributed meaningfully to regional security stability in Southeast Asia.